Autonomous learning in Covid 19 season: A look at the Faculty of Systems Engineering of a private university in Lima - González Andrade, Rodolfo Arturo; Rosario Pacahuala, Emilio; Rufino Gabriel, Margarita; Medina Gamero, Aldo (LACCEI, 2024)
Abstract: The new situation of confinement as a result of covid 19, forced new university students to a purely virtual education. Universities had to modify their curricula, some of which for several years had been providing face-to-face education with some virtual courses, which led to the development of autonomous students in their learning, as required by this new post-pandemic society. The objective of the article is to describe the presence of autonomous learning in novice students of the first cycle and experienced students of the tenth cycle of the Faculty of Systems Engineering of a private university in Lima during the health emergency season. The research method is descriptive, with samples of two classrooms, one of 116 and the other of 12 students, using a questionnaire as an instrument in the middle of the cycle 2021 - 1. The results obtained in the two groups show that the group of the first cycle presents many energies. However, there are several gaps in terms of autonomous learning and with the passing of the cycles it is getting stronger until reaching high levels, so it is necessary to continue and enhance this methodology, which has been carried out with the service of specialist teachers and institutional policies in this house of higher education.